Gestão de risco cambial no ambiente corporativo: aplicação da análise de componentes principais para a gestão do risco cambial em Trading Companies brasileiras - Santos, João Henrique Perez Santos (2014)
The present paper aims at analyzing the adoption of portfolio immunization techniques for the FX hedge management in the corporate environment of a Trading Company using in a pioneering way the Principal Component Analysis applied to the FX curve as an alternative to the frequently used models of hedge using back-to-back and duration-hedge strategies which show some deficiencies on its management. To exemplify the effectiveness of the immunization strategy, it was created a random portfolio of FX exposures dated at 02/01/2013 that comprised 200 transactions with notional between US$5 million and –US$10 million, for maturities also aleatory between 03/06/2013 and 01/12/2014 maturing on the first business day of each month. The results of the Principal Component Analysis showed that for the 3 periods analyzed, 1,2 and 3 years, the first three components explained, respectively, 97.17%, 97.90% e 97.53% of the variability of the FX curve. With respect to the portfolio immunization, the strategy that used the principal component methodology seemed to be extremely effective, when compared to the back-to-back strategy, allowing it to be used in the corporate environment. The hedge strategy using the Principal Component Analysis for 1, 2 and 3 years and the Duration Hedge strategy showed an effectiveness of, respectively, 101.3%, 99.47%, 97.64% and 99.24% for the period of analysis and an amplitude on its daily effectiveness of 8.62%, 7.79%, 8.45% e 19.21%, which shows a superiority of the strategy when compared to the Duration Hedge. The results obtained from this paper are of great relevance for the corporate risk management in the local market.